Peningkatan Motivasi Belajar Siswa Melalui Kreativitas dan Kompetensi Pedagogik Guru - Saring (STIT Sirojul Falah Bogor, 2023)
The purpose of this Research is to Analysis how influential between Dependent Variable and Independent Variable and find how to increase student learning motivation from research how influential between variables; (1) Teacher creativity of student learning motivation, (2) Teacher pedagogical completence of student learning motivation dan (3) creativity and teacher pedagogical completence of student learning motivation. From this research the writer to tested, to proved and to analyzed so how to make a relationships cause and effect to influence of teacher creativity and pedagogical competence of student learning motivation. The population in this research we teachers and student regency West Java. The method in this reaserch is survei causal with data analysis techniques using path analysis. The results of data analysis are; (1) There are a positive and significant influence between teacher creativity of student learning motivation, (2) There are positive and significant direct effect of teacher pedagogical competence to student learning motivation dan (3) There are a positive and significant direct effect between creativity and teacher pedagogical competence of student motivation. The increasing student motivation will have and impact to student achievement outcomes. Keywords: Learning Achievement, Path Analysis Model, Educational Management, Learning Strategic Management.